Rotigotine transdermal patch in Chinese patients with advanced Parkinson's disease: A randomized, double-blind, placebo-controlled pivotal study. (November 2017) - Zhang, Zhen-Xin; Liu, Chun-Feng; Tao, En-Xiang; Shao, Ming; Liu, Yi-Ming; Wang, Jian; Asgharnejad, Mahnaz; Xue, Hai-Bo; Surmann, Erwin; Bauer, Lars
Abstract: Introduction: Rotigotine was demonstrated to be efficacious and well-tolerated in three placebo-controlled studies (CLEOPATRA-PD/PREFER/SP921) of patients with advanced-stage Parkinson's disease (PD), most of whom were Caucasian. This multicenter phase 3 study (SP1037;NCT01646255 ) was the first to investigate the efficacy and safety of rotigotine in Chinese patients with advanced-stage PD. Methods: Chinese patients with PD, inadequately controlled on levodopa (stable dose ≥200 mg/day), with ≥2.5 h/day "off" time, and Hoehn & Yahr stage 2–4, were randomized 1:1 to receive transdermal rotigotine or placebo, titrated over ≤7 weeks, maintained at optimal/maximum dose (4–16 mg/24 h) for 12 weeks. Primary efficacy variable: mean change in absolute "off" time (according to patient diaries) from baseline to end of maintenance. Safety variables included adverse events (AEs) and discontinuations due to AEs. Results: 346 patients were randomized and 89.9% completed the study (87.8% placebo; 92.0% rotigotine). All were Chinese (58.7% male; mean ± SD age: 62.2 ± 8.9 years; mean ± SD time since PD diagnosis: 6.62 ± 3.70 years). Rotigotine significantly reduced "off" time vs placebo (LS mean [95% CI] treatment difference: −1.20 h/day [−1.83,  −0.57]; p = 0.0002), and resulted in more responders (≥30% decrease in "off" time: 36.9% placebo; 48.8% rotigotine; p = 0.0269). AEs were reported for 86 (50.0%) placebo- and 103 (59.2%) rotigotine-treated patients; 15 discontinued due to AEs (placebo 7; rotigotine 8). The most common AEs (≥5%) were dizziness, nausea, pruritus, and dyskinesia. Conclusions: Rotigotine was efficacious in Chinese patients with advanced-stage PD as add-on therapy to levodopa, significantly reducing "off" time vs placebo; the treatment difference was similar to that observed in previous studies of mainly Caucasian patients. Rotigotine was generally well-tolerated and had a similar AE profile to those observed in previous studies. Highlights: This is the first study of rotigotine in Chinese patients with advanced-stage PD. Rotigotine significantly reduced "off" time vs placebo. There was a higher proportion of responders (≥30% less "off" time) with rotigotine. Rotigotine was generally well-tolerated, with no new safety signals. Efficacy/safety profiles of rotigotine were similar to those in Caucasian patients.